2017
DOI: 10.1093/mnras/stx1192
|View full text |Cite
|
Sign up to set email alerts
|

On the magnetic field evolution time-scale in superconducting neutron star cores

Abstract: We revisit the various approximations employed to study the long-term evolution of the magnetic field in neutron star cores and discuss their limitations and possible improvements. A recent controversy on the correct form of the induction equation and the relevant evolution timescale in superconducting neutron star cores is addressed and clarified. We show that this ambiguity in the estimation of timescales arises as a consequence of nominally large terms that appear in the induction equation, but which are, i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 29 publications
3
36
0
Order By: Relevance
“…Core-field evolution is a much more vexed issue, mainly due to the uncertain role played by superfluid components (which are present even in magnetars younger than any observed to date; Ho et al (2012)). There are debates about whether any core process is fast enough to be relevant to magnetars; providing arbitration of the dispute is beyond the scope of this paper, but for a flavour of the recent literature see, e.g., Jones (2006); Glampedakis et al (2011b); Graber et al (2015); Gügercinoglu & Alpar (2016); Dommes & Gusakov (2017); Passamonti et al (2017); Castillo et al (2017); Ofengeim & Gusakov (2018). There is also little understanding about how core and crust are linked, and the physics at the boundary that separates them.…”
Section: Introductionmentioning
confidence: 99%
“…Core-field evolution is a much more vexed issue, mainly due to the uncertain role played by superfluid components (which are present even in magnetars younger than any observed to date; Ho et al (2012)). There are debates about whether any core process is fast enough to be relevant to magnetars; providing arbitration of the dispute is beyond the scope of this paper, but for a flavour of the recent literature see, e.g., Jones (2006); Glampedakis et al (2011b); Graber et al (2015); Gügercinoglu & Alpar (2016); Dommes & Gusakov (2017); Passamonti et al (2017); Castillo et al (2017); Ofengeim & Gusakov (2018). There is also little understanding about how core and crust are linked, and the physics at the boundary that separates them.…”
Section: Introductionmentioning
confidence: 99%
“…Other recent works (Graber et al 2015;Elfritz et al 2016) have also shown that, without considering ambipolar diffusion, the magnetic flux expulsion from the NS core with superconducting protons is very slow. In Passamonti et al (2017a) the various approximations employed to study the long-term evolution of the magnetic field in NS cores were revisited, solving a recent controversy (Graber et al 2015;Dommes and Gusakov 2017) on the correct form of the induction equation and the relevant evolution timescale in superconducting NS cores.…”
Section: Ambipolar Diffusion In Neutron Star Coresmentioning
confidence: 99%
“…The magnetic dynamics of the Type II superconductor in coupling with the rotational dynamics of the neutron superfluid is a complicated problem for which the detailed solution on all different timescales is not known (Passamonti et al 2017). The essentials relevant for the evolutionary scenario of Srinivasan et al (1990) were presented in an important paper by Ruderman et al (1998).…”
Section: Flux-vortex Pinningmentioning
confidence: 99%
“…The rotational (solenoidal) electric field E = −1/c(∂A/∂t) which plays the leading role in the dynamics of magnetic field decay (Passamonti et al 2017) is set up by the radial flow of flux lines in the case of a Type II superconductor:…”
Section: Flux-vortex Pinningmentioning
confidence: 99%